2007
DOI: 10.1097/brs.0b013e318067e35e
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Irrigation in Pyogenic Spondylitis Accompanied by Iliopsoas Abscess

Abstract: This treatment is minimally invasive and useful in carefully selected patients with pyogenic spondylitis complicated by iliopsoas abscess.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Percutaneous suction, aspiration, drainage and continuous irrigation with local administration of antibiotic agents have also been found to be effective in patients with early-stage pyogenic spondylitis (5,17). Such techniques have also been used for the treatment of pyogenic spondylitis accompanied by iliopsoas abscess (6,7). However, the continuous irrigation restrained the patients to their beds and limited their postoperative ambulation and activities.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Percutaneous suction, aspiration, drainage and continuous irrigation with local administration of antibiotic agents have also been found to be effective in patients with early-stage pyogenic spondylitis (5,17). Such techniques have also been used for the treatment of pyogenic spondylitis accompanied by iliopsoas abscess (6,7). However, the continuous irrigation restrained the patients to their beds and limited their postoperative ambulation and activities.…”
Section: Discussionmentioning
confidence: 97%
“…A few reports have also described the use of such techniques in treating pyogenic spondylitis accompanied by iliopsoas abscess or marked bone destruction (6,7). However, continuous irrigation restrains the patients to their beds and limits postoperative ambulation and activities.…”
Section: Introductionmentioning
confidence: 97%
“…[36,37] However, this technique lacks endoscopic monitoring for debridement of the lesion site. Furthermore, the continuous irrigation confines the patients to their beds and limits postoperative ambulation and activities.…”
Section: Efficacy Of Pedd For Complicated Infectious Spondylodiscitismentioning
confidence: 99%
“…[27,28] Similarly, several minimally invasive spinal techniques had been developed and used to treat infectious spondylodiscitis. [29][30][31][32][33][34][35][36][37] CT-guided percutaneous catheter drainage, [19] percutaneous transpedicular discectomy and drainage, [29,32] percutaneous drainage and continuous irrigation, [33,36] percutaneous suction aspiration and drainage, [34,37] and automated percutaneous flexible nucleotome debridement [30,35] through a unilateral or bilateral posterolateral approach have been reported as efficient and safe procedures in the management of early-stage spondylodiscitis. However, these procedures lack intraoperative virtual images monitoring for debridement of the lesion site.…”
Section: Minimally Invasive Spinal Surgery For Spondylodiscitismentioning
confidence: 99%
“…They concluded that it is a useful and minimally invasive technique for the conservative treatment of lumbar discitis, although the causative pathogens could be identified in only 45 % of their cases. Percutaneous suction, aspiration, drainage, and continuous irrigation with local administration of antibiotics have also been found to be effective in patients with an early-stage pyogenic spondylitis and even spinal infection accompanied by iliopsoas abscesses [9][10][11][12]. However, the continuous irrigation restrained the patients to their beds and limited their postoperative ambulation and activities.…”
Section: Introductionmentioning
confidence: 99%